(3GdMOhO GdOSJhQjI Hjf GdSdWJjf GdJTQjYjI hGdbVGFjI HOhdI bWQ (B: s (3OQGSI ebGQfI (B/ s - (3MeO Hf GMeO GdefGYi s; (3LGHQ LGO fUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JfGhd GdHGMK OQGSI GdMOhO GdOSJhQjI Hjf GdSdWJjf GdJTQjYjI hGdbVGFjI HOhdI bWQ hGXgQJ GdOQGSI eGgjI GdbGYOI GdOSJhQjI hWHjYJgG Ke HjGf eHOC GdaUd Hjf GdSdWGJ ai GdOhd eMd GdebGQfI Ke GdJejR Hjf GdYed GdJTQjYi hGdYed GdbVGFi hcPdc JfGhdJ GdOQGSI MOhO JOGNd GdHQdeGf ai TDhf GdSdWI GdbVGFjI heHOG GdGNJUGU GdJTQjYi HJfXje GdbVGA ceHOG YGe ceG Je HjGf eOi bOQg GddhGFM GdUGOQI ai GdXQha GdYGOjI Gh GdGSJKfGFjI dJfXje GdbVGA ceG JfGhdJ GdQSGdI TQhW Jhdjg GdbVGA hWQb GdJYjjf ai OhdI bWQ hGdOhdI GdebGQfIs
(3jTJed Ydi edGMb(B: (3UaMI (B471-503s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2009s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B505-522s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdMOhO GdOSJhQjI s; (3JONd GdbVGA ai GdSdWI GdJTQjYig s; (3TfDf GdSdWI GdbVGFjI s; (3eHOC YOe bGHdjI GdbVGA ddYRds; (3GdVeGfGJ GdbGfhfjIs; (3GdQbGHI Ydj OSJhQjI GdbhGfjfs; (3GdVeGfGJ GdSjGSjIs; (3GdQCj GdYGes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes